Rerata Kenaikan Berat Badan Per Hari pada Bayi Berat Lahir Rendah dengan Perawatan Metode Kanguru - Selviany, Melissa; Allenidekania, Allenidekania; Rustina, Yeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the weight gain of premature babies and Low Birth Weight (LBW) babies after carrying out Kangaroo Method Treatment (PMK). The research method used is a systematic review through searching for articles from the ProQuest, ScienceDirect, PubMed, Sage Journal and Taylor & Francis Online databases. The results of the study showed that FMD intervention would be able to increase the weight of premature babies more than routine care. In conclusion, by doing PMK regularly, the baby's weight will increase. A duration of six hours has been proven to be more effective in increasing a baby's weight than a duration of one hour. PMK can be used as a cheap complementary care intervention for premature or low birth weight babies when care facilities are limited. Keywords: low-birth-weight, kangaroo care, premature baby, weight gain